Correlation between Serum Mid-Regional Pro-Adrenomedullin and Sequential Organ Failure Assessment (SOFA) Score in Patient with Sepsis (Majalah Kedokteran Bandung, 2019)
Most sepsis will develop into multi organ failure (MOF). To assess manifestation of MOF, SOFA score that includes several laboratory parameters for each organ is used. However, this requires time and is also costly. Recently, Mid-Regional Pro-Adrenomedullin (MR proADM) biomarkers are stated to be an alternative marker of MOF in sepsis because MR proADM is secreted by endothelials that may increase in sepsis or bacterial infection. The aim of this study was to analyze the correlation between serum MR proADM levels and SOFA score. This was a cross-sectional  observational analytical study conducted in Dr. Hasan Sadikin General Hospital (RSHS) Bandung from August 2017 to July 2018. This study was a part of the bigger sepsis biomarker study. Samples used in this study consisted of 50 stored serum from the Sepsis Biomarker study in which the MR proADM was measured. Analysis using Spearman’s correlation test showed a moderate positive correlation between serum MR proADM level and SOFA score (r = 0,582, p=0.000), showing that MR proADM serum was directly proportional to SOFA score. It is concluded that MR proADM can be considered as one of the biomarkers for multi organ failure.Korelasi Kadar Mid Regional ProAdrenomedullin Serum dengan Skor Sequential Organ Failure Assessment (SOFA) pada Penderita SepsisSebagian besar sepsis akan berlanjut menjadi multi organ failure (MOF). Untuk mengetahui MOF digunakan skor SOFA yang memerlukan beberapa parameter laboratorium untuk tiap-tiap organ dan membutuhkan waktu dengan biaya yang mahal. Saat ini diketahui biomarker Mid Regional proAdrenomedullin (MR proADM) dapat digunakan sebagai biomarker MOF pada sepsis karena MR proADM disekresi oleh endotel yang akan meningkat pada keadaan sepsis atau infeksi bakteri. Tujuan penelitian ini mengetahui korelasi kadar MR proADM serum dengan skor SOFA. Penelitian ini bersifat observasional analitik dengan rancangan potong lintang dilaksanakan di RSUP Dr. Hasan Sadikin (RSHS) Bandung pada bulan Agustus 2017 sampai Juli 2018. Penelitian ini bagian dari payung penelitian â€œBiomarker pada sepsisâ€. Bahan pemeriksaan berupa bahan biologis tersimpan sebanyak 50 sampel dan dilakukan pemeriksaan MR proADM. Hasil analisis menggunakan Spearman’s correlation test menunjukkan korelasi positif sedang antara kadar MR proADM serum dan skor SOFA (r=0,582; p=0,000). Hal ini menunjukkan semakin tinggi kadar MR proADM serum maka semakin tinggi skor SOFA. Simpulan, terdapat korelasi positif sedang dan bermakna antara MR proADM dengan skor SOFA, sehingga MR proADM dapat dipertimbangkan sebagai salah satu biomarker pada multi organ failure.
Keywords: MOF; MR proADM serum; sepsis; SOFA score